Auditing NICU nursing documentation in hospitals of Babol University of Medical Sciences - Yosefi Roshan, Horieh; Zagheri Tafreshi, NICU M.Sc student. Department of Pediatr; Noorian, Manijeh; Shakeri4, Nezhat (Advances in Nursing & Midwifery, 2015)
Background and aim: Documentation is one of the nurses’ professional tasks, which is an essential component of medical evidence and patient’s record; it sounds that nothing can reflect the total amount of nursing care giving patients as documentation does. The aim of this study was to audit the nurses’ documentation in NICU at hospitals affiliated to Babol University of Medical Sciences and health service, 2012. Method & Materials: This study was a descriptive survey, 400 nursing documentations of the two NICUs of two hospitals of Babol University of Medical Sciences were selected through time sampling. The data were collected by a check list which was developed by the researcher in accordance with recent national and international standards of nursing documentation. The validity of the check list was assured by a panel of experts .Reliability was determined by inter rater method. Completeness of records was observed and scores as: not acceptable (0-49), somewhat acceptable (50-74) and acceptable (75-100). Findings: The study indicated that 49.3% of nursing documents complied with standards of documentations. Which indicates a poor quality of documentation in NICUs of hospitals in this study. Conclusion: Findings of the study showed that there is a need to educate Nurses in NICUs on documentation principles and more supervision and feedback by managers and leaders Keywords: Documentation, Nursing, Auditing, NICU.